Spatial analysis of traffic accidents on the main road between Tasluja – Dukan for the years (2020-2024) - Saleh, Adnan Ali Mohammed; Goran, Bassem Qasim Sulaiman; Hamad, Pashtiwan Jawad; Ali, Garmian Hussein (Sulaimani Journal for Humanities, 2026)
Road networks are considered to be one of the most important services that every country and city pays great attention to, because it has the ability to achieve economic, cultural and social development The road is considered to be one of the strategic roads in the Kurdistan Region, and plays an important role in connecting the main center between the capital and Sulaimani province, due to the increased traffic density in the area, the number of traffic accidents (Collisions) are different on this road, which is a serious threat to the safety of drivers, passengers and citizens. The aim of this study is to show all the accidents recorded during the years (2020-2025) in the study area, based on the data and information obtained, as well as comparison between years and analysis of all transportation accidents Traffic is on this road for the years 2020 to 2024, in order to understand the local factors, relying on speed cameras and point-to-point cameras, because with the arrival of these two factors traffic accidents have decreased significantly. This is due to the presence of fixed cameras and quarantine, but for the year (2024) due to point-to-point cameras only (4) accidents were recorded, which proves that point-to-point cameras are the best option for drivers, citizens and pedestrians The most important results are that in 2021-2023, despite taking three years of traffic accidents, but compared to previous years, the number of accidents is lower, due to the installation of fixed cameras, quarantine and closure of schools and government institutions The installation of point-to-point cameras has a significant impact on reducing traffic accidents, so that in just one year, for the year (2024) only (4) different accidents have been recorded
Keywords: Location Analysis; Transportation Road Network; Traffic Accidents; Dukan City Point to Point Camera